Morphometric Variations of Chalcorana chalconota (Schlegel, 1837) in Four Populations in Jatimulyo Kulon Progo - Hanifuddin, Afnan Saud; Aini, Khuratul; Suwartiningsih, Nurul (Journal of Biotechnology and Natural Science, 2022)
Jatimulyo is an ecotourism area consisting of several areas, each of which has a different height and abiotic factors. This can affect the morphometric character of frogs including Chalcorana chalconota. Research on specific morphometric variations of Chalcorana chalconota in Jatimulyo ecotourism has never been conducted. The purpose of this study was to analyze the distinguishing character of four frog populations as well as analyze the morphometric variation of the Chalcorana chalconota frog in Jatimulyo ecotourism. The research samples were taken using the visual encounter survey method and direct collection in the field in all four populations. Morphometric measurements use 32 characters. The measurement data obtained were analyzed using the Kruskall-Wallis test followed by UPGMA to see dissimilarity using the MVSP 3.1 program. The results showed that of the 32 characters observed and analyzed, there were nine characters that had a p<0.05 value which means it is significant to distinguish the four populations. The nine characters are (HW), (TD), (MFE), (MBE), (HAL), (LAL), (FOL), (IN), (MTL). LK, DT, JMMD, JMMB, JIN, PMD, PBR, PTJ4, PTM. The frog Chalcorana chalconota population of Kembang Soka has a high morphometric similarity with the population of Kedung Pedut. The Mudal River Population and the Bull Kedung Population have a considerable morphometric similarity with the Soka Flower and Pedut Flower Populations. This study can be concluded that the morphometric variation of Chalcorana chalconota in Jatimulyo ecotourism is influenced by altitude factors.